Iron-based nano-motor loaded with antitumor drug, preparation method and application
By loading dihydrochlorophene e6 on the nanomotor and combining ferrodynamic, photodynamic and photothermal therapy, the problem of poor tumor suppression effect in the prior art is solved, and efficient tumor treatment effect is achieved.
Patent Information
- Application Number
- CN202411941117.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, nanomotors loaded with dihydrophenoephine e6 have poor inhibitory effects on tumors, single carrier effect, simple treatment mode, no targeting, and low efficiency of tumor cells to absorb drugs.
Iron-based nanomotor is used to load dihydrophen e6 onto the nanomotor, causing ferrous death of tumor cells through the ferrous ions of the nanomotor, and combined with photodynamic and photothermal treatment, it enhances drug enrichment and penetration ability in tumor tissues.
It significantly improved the killing effect of tumor cells, achieved ferrodynamic-photodynamic-photothermal combined treatment, enhanced the absorption of anti-tumor drugs by tumor cells, and improved the targeting and efficiency of treatment.
Smart Images

Figure CN119701012A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of an iron-based nanomotor loaded with anti-tumor drugs, and belongs to the field of biomaterials. Background Art
[0002] Cancer has become the main cause of human death and reduced life expectancy. At present, cancer treatment methods mainly include surgical treatment, chemotherapy, radiotherapy, etc. These methods have made great progress and effectively extended the survival time of cancer patients, but they still have some problems, such as postoperative recurrence, incomplete treatment or side effects. Reactive oxygen species (ROS) refers to the general term for oxygen-containing free radicals and peroxides that are easy to form free radicals in the body and are related to oxygen metabolism, mainly including peroxides, superoxides, hydroxyl free radicals, and singlet oxygen. The latest research has found that a large amount of reactive oxygen species in cells can cause oxidative damage to cells and induce tumor cell death. At present, anti-tumor treatment methods based on reactive oxygen species include chemodynamic, sonodynamic, photodynamic and other therapies, and their efficacy is seriously dependent on acidic pH (such as pH = 2-4), hydrogen peroxide levels, tissue oxygen content, etc. Among them, phototherapy is an emerging anti-tumor treatment method. Its principle is to use near-infrared light to irradiate photothermal agents to generate high temperatures or irradiate photosensitizers to generate reactive oxygen species, thereby killing tumor cells. Phototherapy has the advantages of strong controllability and good targeted killing effect. However, the tumor microenvironment not only exhibits properties such as hypoxia, weak acidity, and high reductiveness, but also has characteristics such as high internal pressure and dense extracellular matrix, which seriously hinder the delivery effect of nanodrugs and actual therapeutic efficiency.
[0003] Recent studies have shown that asymmetric nanoparticles with photothermal properties will generate a thermal gradient field around them under near-infrared light irradiation, showing a "thermophoresis" phenomenon, that is, the directional movement of nanoparticles is accelerated. Nanoparticles with this property are called nanomotors, and using them as drug carriers can significantly improve the accumulation of nanodrug systems in tumors and the penetration of drugs in tumor tissues, which is beneficial to tumor cells' uptake of drugs and improves the efficacy.
[0004] Chlorin e6 is a photosensitizer with excellent comprehensive performance. Under 660-nanometer laser irradiation, it can produce a large amount of reactive oxygen, which can effectively kill tumor cells. If chlorin e6 can be loaded on a nanomotor, its killing effect on tumor cells will be further improved. Recent studies have shown that by constructing a carrier material and loading chlorin e6 to the tumor microenvironment, tumor cells can better absorb drugs and kill tumor cells. However, this method has problems such as a single carrier effect, a simple treatment mode, no targeting, and low efficiency of drug absorption by tumor cells, and it cannot effectively inhibit tumors. Summary of the invention
[0005] In order to solve the technical problem that the nanomotor loaded with dihydrochlorin e6 in the prior art has poor inhibitory effect on tumors, the purpose of the present invention is to provide an iron-based nanomotor loaded with anti-tumor drugs, a preparation method and an application, which can load the photosensitizer dihydrochlorin e6, which has a prominent "thermophoresis" phenomenon under near-infrared light irradiation, and not only has photothermal therapy, chemodynamic therapy, photodynamic therapy and ferroptosis treatment capabilities, but also can enhance the enrichment and penetration capabilities in tumor tissues under near-infrared light irradiation, and significantly improve the tumor cell killing effect. The present invention induces tumor cell ferroptosis through the ferrous ions contained in the nanomotor, and then realizes ferroptosis-photodynamic-photothermal combined therapy. At the same time, the iron-based nanomotor is modified with a hyaluronic acid derivative to enhance the targeting of the iron-based nanomotor. The characteristics of its directional movement under light drive can enhance the ability of the iron-based nanomotor to penetrate tumor cells and enter the inside of tumor cells.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer comprises the following steps:
[0008] Preparation of hemispherical hollow vesicle-like iron-based nanomotors self-assembled by metal-hydrazide coordination;
[0009] The metal-hydrazide coordinated self-assembled hemispherical hollow vesicle-like iron-based nanomotor was modified with dopamine hyaluronic acid and then loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer.
[0010] Furthermore, the metal-hydrazide coordinated self-assembled hemispherical hollow vesicle-shaped iron-based nanomotor was prepared by the following process:
[0011] The ethanol solution of ferrous chloride tetrahydrate and the ethanol solution of organic small molecules containing hydrazide groups are mixed evenly, and placed in a shaker for reaction at 20-50° C. for 10-16 hours to obtain a hemispherical hollow vesicle-shaped iron-based nanomotor self-assembled by metal-hydrazide coordination.
[0012] Furthermore, the organic small molecule containing a hydrazide group is 3,3'-dithiodipropionyl hydrazide.
[0013] Furthermore, the molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide is 0.3-3:1.
[0014] Further, dopaminized hyaluronic acid is prepared by the following process:
[0015] Adding sodium periodate to the sodium hyaluronate aqueous solution, adding ethylene glycol after reaction, stirring, dialyzing, and freeze-drying to obtain aldehyded hyaluronic acid;
[0016] Dopamine hydrochloride is added to the aqueous solution of aldehyde-modified hyaluronic acid, and the mixture is placed in a shaker at 20-50° C. for reaction for 5-60 minutes. The dopaminated hyaluronic acid is obtained by dialyzing and freeze-drying.
[0017] Furthermore, the dosage ratio of sodium hyaluronate, sodium periodate and ethylene glycol is 1 g: 0.1-1.0 g: 2 mL, the reaction temperature for aldehyde-forming hyaluronic acid is 30° C., and the reaction time is 8 hours.
[0018] Furthermore, the mass concentration of the aldehyde-hydrated hyaluronic acid aqueous solution is 0.1-10%, and the dosage of the aldehyde-hydrated hyaluronic acid aqueous solution and dopamine hydrochloride is 10 ml: 0.1-10 mg.
[0019] Furthermore, the metal-hydrazide coordinated self-assembled hemispherical hollow vesicle-shaped iron-based nanomotor is modified with dopaminated hyaluronic acid, and then loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer, comprising the following steps:
[0020] Under ultrasound, a hemispherical hollow vesicle iron-based nanomotor ethanol suspension self-assembled by metal-hydrazide coordination is added to a dopaminized hyaluronic acid aqueous solution and reacted for 10-60 minutes to obtain a light-driven iron-based nanomotor loaded with a photosensitizer;
[0021] The light-driven iron-based nanomotor loaded with a photosensitizer was dispersed in a saturated chlorin e6 ethanol solution and reacted for 48 hours to obtain the light-driven iron-based nanomotor loaded with a photosensitizer.
[0022] A photosensitizer-loaded light-driven iron-based nanomotor, wherein the drug loading rate of dihydrochlorin e6 in the photosensitizer-loaded light-driven iron-based nanomotor is 5%-20%, the particle size of the photosensitizer-loaded light-driven iron-based nanomotor is 80-200nm, the zeta potential is -10.8mV, the drug loading is 5-20%, and the power of 808nm laser is 2W / cm 2 Under irradiation, the mean square displacement velocity of the light-driven iron-based nanomotor loaded with photosensitizer is 40 μm 2 / s.
[0023] Application of a light-driven iron-based nanomotor loaded with a photosensitizer in the preparation of anti-tumor drugs.
[0024] Furthermore, the anti-tumor drug is an anti-liver cancer drug.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] In the present invention, a metal ion alcohol solution and an organic small molecule containing a hydrazide group are uniformly mixed in ethanol, placed in a shaker for reaction, centrifuged, and washed to obtain metal-hydrazide self-assembled asymmetric structure nanoparticles with strong controllability of particle size, which solves the problem that the preparation method of spherical nanoparticles is complicated, the particle size distribution is uneven, and the nanoparticles cannot achieve directional movement. Anti-tumor drugs are loaded on hemispherical hollow nanoparticles to form iron-based nanomotors. Iron-based nanomotors have photothermal effect, photodynamic effect and ferroptosis induction ability, realize the organic integration of multiple treatment modes, and significantly improve the anti-tumor treatment effect; the iron-based nanomotors of the present invention have the characteristics of simple preparation process, mild reaction conditions, high photosensitizer loading, good stability in aqueous phase, etc., which significantly enhance the killing effect of light-driven iron-based nanomotors loaded with photosensitizers on tumor cells.
[0027] In the present invention, the hyaluronic acid shell with tumor targeting function is modified on the nanomotor through hydrazide-iron coordination, which can not only maintain stability in the circulatory system to prevent premature drug leakage, but also actively target tumor tissue and quickly remove it in the tumor, which is beneficial to the internal nanomotor thermophoresis ability; the prepared iron-based nanomotor has dissociation and drug release behavior with dual responsiveness to acidic pH and reducing glutathione, and can respond to weakly acidic and reducing tumor microenvironments to better exert therapeutic effects; and under near-infrared light irradiation, a photothermal effect occurs, which stimulates the nanomotor to move in a directional manner, enhances the absorption of anti-tumor drugs by tumor cells, and realizes ferroptosis-photodynamic-photothermal combined treatment of tumor cells, which can be used in the preparation of anti-tumor drugs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are scanning electron microscope and transmission electron microscope images of the hemispherical hollow nanoparticles of Example 2. Among them, (a) is a transmission electron microscope image of the hemispherical hollow nanoparticles; (b) is a scanning electron microscope image of the hemispherical hollow nanoparticles.
[0029] Figure 2 It is a comparison diagram of the photothermal heating curves of nanoparticles with different morphologies in Example 2 and Example 4, wherein (a) is the photothermal heating curve of the hemispherical hollow nanoparticles in Example 2; and (b) is the photothermal heating curve of the solid spherical nanoparticles in Example 4.
[0030] Figure 3 It is the thermophoresis phenomenon of Example 5 under near-infrared light irradiation, where (a) is the motion trajectory of the iron-based nanomotor under different laser irradiation powers, and (b) is the change of the mean square displacement of the iron-based nanomotor with time under different laser irradiation powers.
[0031] Figure 4 This is a transmission electron microscope image of the nanomotor in Example 5.
[0032] Figure 5 It is the particle size distribution of nanoparticles in each stage in Example 1 and Example 5, where (a) is the particle size distribution of hemispherical hollow nanoparticles; (b) is the particle size of hyaluronic acid hemispherical hollow nanoparticles; (c) is the particle size of iron-based nanomotors.
[0033] Figure 6 It is the Zeta potential of the hemispherical hollow nanoparticles, hyaluronic acid hemispherical hollow nanoparticles, and iron-based nanomotors in Example 5.
[0034] Figure 7 This is the ultraviolet absorption spectrum of the iron-based nanomotor in Example 5.
[0035] Figure 8 The particle size and Zeta potential of the iron-based nanomotor obtained in Example 5 change with time in water at different times.
[0036] Fig. 9 These are the photothermal temperature rise curves of the dopamine-modified hyaluronic acid-modified hemispherical hollow nanoparticles and the hyaluronic acid-modified hemispherical hollow nanoparticles in Example 5.
[0037] Fig.10 This is a test of the photodynamics of the iron-based nanomotor of Example 5, wherein (a) is the change in absorbance of 1,3-diphenylisobenzofuran with illumination time; (b) is the change in absorbance of 1,3-diphenylisobenzofuran with illumination time after the addition of the iron-based nanomotor.
[0038] Fig.11 This is the electron paramagnetic resonance test of the nanomotor in Example 5.
[0039] Fig.12 This is the killing effect of different concentrations of iron-based nanomotors in Example 5 on Hepa1-6 cells (mouse liver cancer cells) in vitro. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0041] The method for preparing a photosensitizer-loaded light-driven iron-based nanomotor of the present invention comprises the following steps:
[0042] An ethanol solution of ferrous chloride tetrahydrate with a concentration of 0.2-0.6 mol / L and an ethanol solution of an organic small molecule containing a hydrazide group (3,3'-dithiodipropionyl hydrazide) with a concentration of 0.002-0.006 mol / L are mixed evenly, wherein the molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide is 0.3-3:1, placed in a shaker at 20-50°C, reacted for 10-16 hours, centrifuged at 8000 rpm-13000 rpm for 5 minutes-20 minutes, washed once and centrifuged again to obtain hemispherical hollow nanoparticles, i.e., hemispherical hollow vesicle-shaped iron-based nanomotors self-assembled by metal-hydrazide coordination, the particle size of the hemispherical hollow nanoparticles is about 80-200 nanometers, the particle size is uniform, the dispersion is good, and the hemispherical hollow nanoparticles can be used to prepare anti-tumor drugs and contrast agents.
[0043] The preparation process of dopaminized hyaluronic acid is as follows: 1 gram of sodium hyaluronate (the molecular weight of hyaluronic acid in sodium hyaluronate is in the range of 10-200 kDa) is dissolved in 100 milliliters of water, followed by adding 0.1-1.0 gram of sodium periodate, and after reacting at 30° C. for 8 hours, 2 milliliters of ethylene glycol are added, and the reaction system is stirred for 1 hour and dialyzed, and freeze-dried to obtain aldehyde-modified hyaluronic acid (aldehyde degree 10%-40%); 10 milliliters of aldehyde-modified hyaluronic acid aqueous solution with a mass concentration of 0.1-10% is prepared, and then 0.1-10 milligrams of dopamine hydrochloride are added, and the mixture is placed in a shaker at 20-50° C. for reaction for 5-60 minutes, and dialyzed through a dialysis bag with a molecular weight cutoff of 1 kDa, and freeze-dried to obtain dopaminized hyaluronic acid with a dopaminized degree of 5%-50%.
[0044] The hemispherical hollow nanoparticles are sequentially modified with hyaluronic acid derivatives (dopamined hyaluronic acid) and loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer. Specifically, the modification process of dopaminated hyaluronic acid is as follows: under ultrasound, 300 microliters of 4 mg / ml nanomotor (hemispherical hollow nanoparticles) ethanol suspension is added to 4 ml of 0.1% dopaminated hyaluronic acid aqueous solution, and after 10-60 minutes of reaction, dopaminated hyaluronic acid-modified hollow nanoparticles are obtained, i.e., light-driven iron-based nanomotor loaded with a photosensitizer.
[0045] The dopaminated hyaluronic acid-modified hollow nanoparticles were dispersed in a saturated chlorin e6 ethanol solution, and reacted for 48 hours to obtain a nanomotor loaded with chlorin e6, i.e., a light-driven iron-based nanomotor loaded with a photosensitizer, wherein the drug loading rate of chlorin e6 (the mass percentage of chlorin e6 in the light-driven iron-based nanomotor loaded with a photosensitizer) was 5%-20%. The particle size of the nanomotor was 80-200nm, the zeta potential was -10.8mV, and the 808nm laser was irradiated at a power of 2W / cm 2Under irradiation, the mean square displacement velocity of the nanoparticles is 40 μm 2 / s.
[0046] The light-driven iron-based nanomotor loaded with a photosensitizer prepared by the present invention can be used for the combined photothermal, photodynamic and ferroptosis treatment of tumors.
[0047] Example 1
[0048] A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.004 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, the molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 1:1. After reacting in a shaker at 37°C for 12 hours, the mixture was centrifuged at 13,000 rpm for 13 minutes to obtain iron-hydrazide coordinated self-assembled hemispherical hollow nanoparticles with poor dispersibility. The particle size analyzer test results showed that the particle size was 120-140 nm, and a large number of nanoparticles were aggregated by transmission electron microscopy.
[0049] Example 2
[0050] A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.003 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, the molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 1:1. After reacting in a shaker at 37°C for 12 hours, the mixture was centrifuged at 13,000 rpm for 13 minutes to obtain hemispherical hollow nanoparticles (Fe-TPH) with improved dispersibility of iron-hydrazide coordination self-assembled. The particle size analyzer test results showed that the particle size was 90-100 nm, and a small amount of nanoparticle aggregation was observed by transmission electron microscopy.
[0051] from Figure 1 As can be seen in (a) and (b), the obtained hemispherical hollow structure nanoparticles are uniform in size, complete in morphology, and have good dispersion. The size of the nanoparticles is about 100 nanometers.
[0052] Example 3
[0053] A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.002 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, the molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 1:1. After reacting in a shaker at 37°C for 12 hours, the mixture was centrifuged at 13,000 rpm for 13 minutes to obtain hemispherical hollow / solid spherical nanoparticles self-assembled by iron-hydrazide coordination.
[0054] Example 4
[0055] A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.003 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, the molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 1:2. After reacting in a shaker at 37°C for 12 hours, the mixture was centrifuged at 13,000 rpm for 13 minutes to obtain iron-hydrazide coordinated self-assembled solid spherical nanoparticles.
[0056] See also Figure 2 In (a) and (b), it can be seen that when the nanoparticles are irradiated with an 808nm laser, the intensity of the photothermal effect of the metal-hydrazide coordinated nanoparticles changes with the change of morphology, indicating that there is a driving force to promote the movement of the nanoparticles. The photothermal effect of hemispherical hollow nanoparticles is much stronger than that of spherical solid nanoparticles.
[0057] Example 5
[0058] A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.003 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, the molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 2:1. After reacting in a shaker at 37°C for 12 hours, the mixture was centrifuged at 13,000 rpm for 13 minutes to obtain iron-hydrazide coordinated self-assembled solid spherical nanoparticles.
[0059] Example 6
[0060] 1) Preparation of hemispherical hollow nanoparticles: A 0.4 mol / L ferrous chloride tetrahydrate ethanol solution was mixed with a 0.003 mol / L 3,3'-dithiodipropionyl hydrazide ethanol solution, with a molar ratio of ferrous chloride to 3,3'-dithiodipropionyl hydrazide being 1:1. The mixture was reacted in a shaker at 37°C for 12 hours, and then centrifuged at 13,000 rpm for 13 minutes to obtain hemispherical hollow nanoparticles with improved dispersibility of iron-hydrazide coordination self-assembled. The particle size analyzer test results showed that the particle size was 80-200 nm, and a small amount of nanoparticle aggregation was observed under transmission electron microscopy.
[0061] 2) Preparation of hyaluronic acid hemispherical hollow nanoparticles: First, prepare a hyaluronic acid derivative: dissolve 1g of sodium hyaluronate in 100ml of water, and add 0.535g of sodium periodate. After reacting at 30°C for 8 hours, add 2ml of ethylene glycol to neutralize the excess unreacted sodium periodate, stir for about 1 hour, put the reactant into a dialysis bag for dialysis, then freeze-dry and weigh to obtain aldehyde-modified hyaluronic acid. Then prepare 10ml of 1wt% aldehyde-modified hyaluronic acid aqueous solution, add 5mg of dopamine hydrochloride, and obtain a dopamine-modified aldehyde-modified hyaluronic acid solution.
[0062] 3) Prepare a 0.1 wt% dopamine / aldehyde-modified hyaluronic acid aqueous solution, ultrasonically disperse the hemispherical hollow nanoparticles prepared in the above step in 300 μl of ethanol, then add 4 ml of the above dopamine-modified aldehyde-modified hyaluronic acid aqueous solution, place in a shaker to react for 30 minutes, and obtain hyaluronic acid-modified hemispherical hollow nanoparticles.
[0063] Preparation of light-driven iron-based nanomotor loaded with photosensitizer: Hyaluronanized hemispherical hollow nanoparticles are dispersed in a saturated ethanol solution of dihydrochlorin e6. Dihydrochlorin e6 can be loaded on the hyaluronanized hemispherical hollow nanoparticles by utilizing the electrostatic adsorption effect. After 48 hours of reaction, the light-driven iron-based nanomotor loaded with photosensitizer is obtained by collecting.
[0064] Comparative Example 1
[0065] The same as Example 6, except that in step 2), dopamine hydrochloride is not added, and the obtained product is recorded as Fe-TPH-Ce6.
[0066] from Figure 3 As can be seen from (a) and (b), when irradiated with 808nm laser, obvious thermophoresis phenomenon of iron-based nanomotor was observed under an optical microscope. In the absence of light, the iron-based nanomotor only performed Brownian motion. When laser irradiation began, the iron-based nanomotor immediately changed its motion state, and the speed of motion increased with the increase of laser power.
[0067] from Figure 4 It can be seen that the hyaluronic acid hemispherical hollow nanoparticles were dispersed in the ethanol solution of dihydrochlorin e6 for 48 hours, then coated with aldehyde hyaluronic acid on the surface, and finally coated with polydopamine in a Tris solution with pH = 8.5. The obtained nanoparticles still maintained good dispersibility and did not show obvious changes in size. Figure 1 Compared with the hemispherical hollow nanoparticles in (a), the surface is rougher, proving that polydopamine is synthesized on the surface of the iron-based nanomotor.
[0068] from Figure 5 As can be seen from (a), (b) and (c), the particle size difference between hemispherical hollow nanoparticles, hyaluronic acid hemispherical hollow nanoparticles and iron-based nanomotors is small. After the formation of iron-based nanomotors, the particle size increases, but generally remains less than 300 nm.
[0069] from Figure 6 It can be seen that the potential also changes significantly when comparing hemispherical hollow nanoparticles, hyaluronanized hemispherical hollow nanoparticles, and iron-based nanomotors, confirming that the hyaluronic acid derivatives are wrapped on the surface of the hemispherical hollow nanoparticles, and dihydrochlorin e6 is loaded on the hyaluronanized hemispherical hollow nanoparticles to eventually form iron-based nanomotors.
[0070] from Figure 7 It can be seen that the UV absorption spectrum shows obvious absorption peaks at 407nm and 667nm, proving that dihydrochlorin e6 is successfully loaded on the hyaluronic acid hemispherical hollow nanoparticles to form iron-based nanomotors with a drug loading rate of 10%.
[0071] from Figure 8 It can be seen that the changes in particle size and potential of the iron-based nanomotors were recorded within 60 hours. The results showed that the iron-based nanomotors had good stability in water and did not agglomerate or degrade.
[0072] from Fig. 9 In (a), (b) and (c), the prepared light-driven iron-based nanomotor loaded with photosensitizer was added to water to form suspensions with concentrations of 50μg / mL, 150μg / mL and 300μg / mL, respectively. As can be seen from Figure (a), the photothermal performance of the iron-based nanomotor was significantly enhanced with the addition of PDA (i.e. polydopamine). The iron-based nanomotor has good photothermal performance. As can be seen from (b), its photothermal effect is positively correlated with the light intensity, and as can be seen from Figure (c), its photothermal effect is positively correlated with the concentration of the iron-based nanomotor.
[0073] from Fig.10 As can be seen from (a) and (b), after adding iron-based nanomotors to the 1,3-diphenylisobenzofuran aqueous solution, the UV absorption curve was measured after laser (635nm) irradiation, and the characteristic peak intensity at 413nm changed. This shows that the iron-based nanomotors produce active oxygen, and Ce6 photodynamics is verified.
[0074] from Fig.11 It can be seen that the iron-based nanomotors exhibited obvious photodynamic performance under laser (635nm) irradiation conditions and demonstrated the production of singlet oxygen.
[0075] Fig.12 It can be seen that the singlet oxygen cannot be detected when the iron-based nanomotor is not illuminated. After illumination, the obvious killing effect of iron-hydrazide self-assembled nanospheres on tumor cells can be detected. The cell viability detection kit (CCK-8) was used to detect the killing effect of iron-hydrazide self-assembled nanospheres on mouse liver cancer Hepa 1-6 cells. Hepa 1-6 cells were cultured at 5×10 3The cells were inoculated on a 96-well plate at a density of 10 cells / well. After 24 hours of conventional culture, different concentrations of nanoparticles were added to each well and cultured for another 24 hours. Then 10 μl of CCK-8 reagent was added to each well and cultured for another hour. The absorbance of each well at 450 nm was detected by an enzyme reader. The percentage of the absorbance of the experimental group relative to the absorbance of the control group (iron-based nanomotor concentration was 0) was the cell viability. As the concentration of iron-based nanomotor increased, the viability of Hepa 1-6 cells gradually decreased. When the concentration of iron-based nanomotor was 100 μg / ml, after irradiation with 635nm and 808nm lasers, respectively, the viability of Hepa 1-6 cells was 20%, indicating that iron-based nanomotor can effectively kill tumor cells.
[0076] Example 7
[0077] A 0.2 mol / L ethanol solution of ferrous chloride tetrahydrate and a 0.002 mol / L ethanol solution of an organic small molecule containing a hydrazide group (3,3'-dithiodipropionyl hydrazide) were mixed evenly, wherein the molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide was 0.3:1. The mixture was placed in a shaker at 20°C for 16 hours, centrifuged at 8000 rpm for 20 minutes, washed once and centrifuged again to obtain hemispherical hollow nanoparticles, i.e., hemispherical hollow vesicle-shaped iron-based nanomotors self-assembled by metal-hydrazide coordination.
[0078] The preparation process of dopaminized hyaluronic acid is as follows: 1 gram of sodium hyaluronate (the molecular weight of hyaluronic acid in sodium hyaluronate is in the range of 10-200 kDa) is dissolved in 100 ml of water, followed by adding 0.1 gram of sodium periodate, reacting at 30°C for 8 hours, then adding 2 ml of ethylene glycol, stirring for 1 hour, dialyzing the reaction system, and freeze-drying to obtain aldehyde-modified hyaluronic acid;
[0079] Prepare 10 ml of 0.1% aldehyde-modified hyaluronic acid aqueous solution, then add 4 mg of dopamine hydrochloride, place in a shaker at 20°C for 60 minutes, dialyze through a dialysis bag with a molecular weight cutoff of 1 kDa, and freeze-dry to obtain dopaminized hyaluronic acid.
[0080] The hemispherical hollow nanoparticles are sequentially modified with hyaluronic acid derivatives (dopamined hyaluronic acid) and loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer. Specifically, the modification process of dopaminated hyaluronic acid is as follows: under ultrasound, 300 microliters of 4 mg / ml nanomotor (hemispherical hollow nanoparticles) ethanol suspension is added to 4 ml of 0.1% mass concentration of dopaminated hyaluronic acid aqueous solution, and after 60 minutes of reaction, dopaminated hyaluronic acid-modified hollow nanoparticles are obtained, that is, light-driven iron-based nanomotor loaded with a photosensitizer.
[0081] The dopaminated hyaluronic acid-modified hollow nanoparticles were dispersed in a saturated chlorin e6 ethanol solution, and after 48 hours of reaction, a nanomotor loaded with chlorin e6, i.e., a light-driven iron-based nanomotor loaded with a photosensitizer, was obtained.
[0082] Example 8
[0083] A 0.5 mol / L ethanol solution of ferrous chloride tetrahydrate and a 0.006 mol / L ethanol solution of an organic small molecule containing a hydrazide group (3,3'-dithiodipropionyl hydrazide) were mixed evenly, wherein the molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide was 3:1. The mixture was placed in a shaker at 50°C for 10 hours, centrifuged at 10,000 rpm for 10 minutes, washed once and centrifuged again to obtain hemispherical hollow nanoparticles, i.e., hemispherical hollow vesicle-shaped iron-based nanomotors self-assembled by metal-hydrazide coordination.
[0084] The preparation process of dopaminized hyaluronic acid is as follows: 1 gram of sodium hyaluronate (the molecular weight of hyaluronic acid in sodium hyaluronate is in the range of 10-200 kDa) is dissolved in 100 ml of water, followed by adding 0.5 gram of sodium periodate, reacting at 30°C for 8 hours, then adding 2 ml of ethylene glycol, stirring for 1 hour, dialyzing the reaction system, and freeze-drying to obtain aldehyde-modified hyaluronic acid;
[0085] Prepare 10 ml of 10% aldehyde-modified hyaluronic acid aqueous solution, then add 0.1 mg of dopamine hydrochloride, place in a shaker at 30°C for reaction for 20 minutes, dialyze through a dialysis bag with a molecular weight cutoff of 1 kDa, and freeze-dry to obtain dopaminized hyaluronic acid.
[0086] The hemispherical hollow nanoparticles are sequentially modified with hyaluronic acid derivatives (dopamined hyaluronic acid) and loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer. Specifically, the modification process of dopaminated hyaluronic acid is as follows: under ultrasound, 300 microliters of 4 mg / ml nanomotor (hemispherical hollow nanoparticles) ethanol suspension is added to 4 ml of 0.1% mass concentration of dopaminated hyaluronic acid aqueous solution, and after 40 minutes of reaction, dopaminated hyaluronic acid-modified hollow nanoparticles are obtained, that is, light-driven iron-based nanomotor loaded with a photosensitizer.
[0087] The dopaminated hyaluronic acid-modified hollow nanoparticles were dispersed in a saturated chlorin e6 ethanol solution, and after 48 hours of reaction, a nanomotor loaded with chlorin e6, i.e., a light-driven iron-based nanomotor loaded with a photosensitizer, was obtained.
[0088] Example 9
[0089] A 0.6 mol / L ethanol solution of ferrous chloride tetrahydrate and a 0.004 mol / L ethanol solution of an organic small molecule containing a hydrazide group (3,3'-dithiodipropionyl hydrazide) were mixed evenly, wherein the molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide was 0.7:1. The mixture was placed in a shaker at 40°C for 12 hours, centrifuged at 12,000 rpm for 5 minutes, washed once and centrifuged again to obtain hemispherical hollow nanoparticles, i.e., hemispherical hollow vesicle-shaped iron-based nanomotors self-assembled by metal-hydrazide coordination.
[0090] The preparation process of dopaminized hyaluronic acid is as follows: 1 gram of sodium hyaluronate (the molecular weight of hyaluronic acid in sodium hyaluronate is in the range of 10-200 kDa) is dissolved in 100 ml of water, followed by adding 0.1 gram of sodium periodate, reacting at 30°C for 8 hours, then adding 2 ml of ethylene glycol, stirring for 1 hour, dialyzing the reaction system, and freeze-drying to obtain aldehyde-modified hyaluronic acid;
[0091] Prepare 10 ml of 5% aldehyde-modified hyaluronic acid aqueous solution, then add 10 mg of dopamine hydrochloride, place in a shaker at 50°C for 5 minutes, dialyze through a dialysis bag with a molecular weight cutoff of 1 kDa, and freeze-dry to obtain dopaminized hyaluronic acid.
[0092] The hemispherical hollow nanoparticles are sequentially modified with hyaluronic acid derivatives (dopamined hyaluronic acid) and loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer. Specifically, the modification process of dopaminated hyaluronic acid is as follows: under ultrasound, 300 microliters of 4 mg / ml nanomotor (hemispherical hollow nanoparticles) ethanol suspension is added to 4 ml of 0.1% dopaminated hyaluronic acid aqueous solution, and after 10 minutes of reaction, dopaminated hyaluronic acid-modified hollow nanoparticles are obtained, that is, light-driven iron-based nanomotor loaded with a photosensitizer.
[0093] The dopaminated hyaluronic acid-modified hollow nanoparticles were dispersed in a saturated chlorin e6 ethanol solution, and after 48 hours of reaction, a nanomotor loaded with chlorin e6, i.e., a light-driven iron-based nanomotor loaded with a photosensitizer, was obtained.
[0094] The preparation method of hemispherical hollow nanoparticles in the present invention is a metal-hydrazide self-assembly nanoparticle preparation method, a metal ion alcohol solution and an organic small molecule containing a hydrazide group are uniformly mixed in ethanol, placed in a shaking table for reaction and centrifuged, washed, and metal-hydrazide self-assembled nanoparticles are obtained. By adjusting the reaction conditions, such as adjusting the concentration of the hydrazide group and the concentration of ferrous ions, nanoparticles with different morphologies can be obtained. Under appropriate conditions, hollow hemispherical vesicle-shaped nanoparticles, i.e., nanoparticles of asymmetric structure can be obtained. The present invention is based on a metal-hydrazide coordination self-assembly method to obtain a nanoparticle with an asymmetric structure, solves the problem that the preparation method of spherical nanoparticles is complicated, the particle size distribution is uneven, and nanoparticles cannot achieve directional motion. Anti-tumor drugs are loaded on hemispherical hollow nanoparticles to form iron-based nanomotors, and photothermal effects occur under near-infrared light irradiation, exciting nanomotors for directional motion, enhancing the absorption of anti-tumor drugs by tumor cells, and realizing iron death-photodynamic-photothermal combined treatment of tumor cells, which can be used in the preparation of anti-tumor drugs.
[0095] The advantages of the present invention are as follows:
[0096] (1) The hemispherical hollow nanoparticles in the present invention are formed by infinite coordination of iron ions and organic hydrazide small molecules through metal-hydrazide, and the particle size is highly controllable;
[0097] (2) The nanomotor in the present invention has photothermal effect, photodynamic effect and ferroptosis induction ability, realizing the organic integration of multiple treatment modes and significantly improving the anti-tumor treatment effect;
[0098] (3) The nanomotor of the present invention has dissociation and drug release behaviors that are dual responsive to acidic pH and reduced glutathione, and can respond to weakly acidic and reducing tumor microenvironments to better exert therapeutic effects;
[0099] (4) The hyaluronic acid shell with tumor targeting function is modified on the nanomotor through hydrazide-iron coordination, which can not only maintain stability in the circulatory system to prevent premature drug leakage, but also actively target tumor tissue and be quickly removed in the tumor, which is conducive to the thermophoresis ability of the internal nanomotor;
[0100] (5) The iron-based nanomotor of the present invention has the characteristics of simple preparation process, mild reaction conditions, high photosensitizer loading, and good stability in aqueous phase, which significantly enhances the killing effect of the light-driven iron-based nanomotor loaded with photosensitizer on tumor cells.
[0101] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0102] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer, characterized in that: The following steps are involved: Preparation of hemispherical hollow vesicle-like iron-based nanomotors self-assembled by metal-hydrazide coordination; The metal-hydrazide coordinated self-assembled hemispherical hollow vesicle-like iron-based nanomotor was modified with dopamine hyaluronic acid and then loaded with dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer.
2. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 1, characterized in that: The hemispherical hollow vesicle-shaped iron-based nanomotors self-assembled by metal-hydrazide coordination were prepared by the following process: The ethanol solution of ferrous chloride tetrahydrate and the ethanol solution of organic small molecules containing hydrazide groups are mixed evenly, and placed in a shaker for reaction at 20-50° C. for 10-16 hours to obtain a hemispherical hollow vesicle-shaped iron-based nanomotor self-assembled by metal-hydrazide coordination.
3. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 2, characterized in that: The organic small molecule containing a hydrazide group is 3,3'-dithiodipropionyl hydrazide.
4. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 3, characterized in that: The molar ratio of ferrous ion to 3,3'-dithiodipropionyl hydrazide is 0.3-3:
1.
5. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 1, characterized in that: Dopaminated hyaluronic acid is produced by the following process: Adding sodium periodate to the sodium hyaluronate aqueous solution, adding ethylene glycol after reaction, stirring, dialyzing, and freeze-drying to obtain aldehyded hyaluronic acid; Dopamine hydrochloride is added to the aqueous solution of aldehyde-modified hyaluronic acid, and the mixture is placed in a shaker at 20-50° C. for reaction for 5-60 minutes. The dopaminated hyaluronic acid is obtained by dialyzing and freeze-drying.
6. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 5, characterized in that: The dosage ratio of sodium hyaluronate, sodium periodate and ethylene glycol is 1g:0.1-1.0g:2mL, the reaction temperature for aldehyde-forming hyaluronic acid is 30°C, and the reaction time is 8 hours.
7. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 5, characterized in that: The mass concentration of the aldehyde hyaluronic acid aqueous solution is 0.1-10%, and the dosage of the aldehyde hyaluronic acid aqueous solution and dopamine hydrochloride is 10 ml: 0.1-10 mg.
8. The method for preparing a light-driven iron-based nanomotor loaded with a photosensitizer according to claim 5, characterized in that: The method comprises the following steps: modifying dopaminated hyaluronic acid with a hemispherical hollow vesicle-shaped iron-based nanomotor self-assembled by metal-hydrazide coordination, and then loading dihydrochlorin e6 to form a light-driven iron-based nanomotor loaded with a photosensitizer. Under ultrasound, a hemispherical hollow vesicle iron-based nanomotor ethanol suspension self-assembled by metal-hydrazide coordination is added to a dopaminized hyaluronic acid aqueous solution and reacted for 10-60 minutes to obtain a light-driven iron-based nanomotor loaded with a photosensitizer; The light-driven iron-based nanomotor loaded with a photosensitizer was dispersed in a saturated chlorin e6 ethanol solution and reacted for 48 hours to obtain the light-driven iron-based nanomotor loaded with a photosensitizer.
9. A light-driven iron-based nanomotor loaded with a photosensitizer prepared according to the method of any one of claims 1 to 8, characterized in that: The drug loading rate of dihydrochlorin e6 in the light-driven iron-based nanomotor loaded with photosensitizer is 5%-20%, the particle size of the light-driven iron-based nanomotor loaded with photosensitizer is 80-200nm, the zeta potential is -10.8mV, the drug loading is 5-20%, and the power of 808nm laser is 2W / cm 2 Under irradiation, the mean square displacement velocity of the light-driven iron-based nanomotor loaded with photosensitizer is 40 μm 2 / s.
10. Use of a light-driven iron-based nanomotor loaded with a photosensitizer prepared according to the method of any one of claims 1 to 8 in the preparation of anti-tumor drugs.
Citation Information
Patent Citations
Modified hyaluronic acid shielded metal organic frame, nano particles, preparation method and application of nano particles
CN108187046A
Metal-hydrazide coordination self-assembly nanosphere as well as preparation method and application thereof
CN114984875A